Comportamento térmico e avaliação microestrutural de concretos leves produzidos com argila expandida - Weber Guadagnin Moravia (2004)
Recently more attention has been given for the influence of the transition zone between aggregate and cement matrix in some properties of the concrete. The majority of the research works in this area didnt study lightweight concrete. This work has with objective evaluate and compare the thermal properties and the microstructure of the transition zone between the light expanded clay aggregate and the cement matrix, withthe microstructure of the transition zone, between limy rocks aggregate and the cement matrix. Assays of compressive strength, chemical analysis, X-ray diffraction, scanning electron microscopy with microprobe analyzer (SEM-EDS), mercury porosimetry, and thermal analysis (TG), (DTG) and (DTA) for lightweight concrete and concrete with normal weight aggregate. The gotten results, had allowed to evaluate the influences ofthe chemical composition and porosity of the expanded clay in the formation of the transition zone with the cement matrix, in the resistance mechanics and thermal properties of the lightweight concrete. One better mechanics interconnection was observed between the expanded clay and the cement matrix. The lightweight concrete presented a reduction of the compressive strength, minor conduction of heat and greater thermal resistance in relation to the conventional concrete